FRI0134 Interleukin-6 Blockade Raises LDL via Reduced Catabolism Rather than via Increased Synthesis – A Cytokine-Specific Mechanism for Cholesterol Changes in Rheumatoid Arthritis. (15th July 2016) - Robertson, J.; Porter, D.; Sattar, N.; Packard, C.; Caslake, M.; McInnes, I.B.; McCarey, D.
Abstract : Background: Rheumatoid arthritis (RA) is associated with significant alteration in circulating lipids, in particular reduced serum total cholesterol and low-density lipoprotein cholesterol (LDL-c) levels. Various RA modulatory therapeutics can increase serum LDL-c; mechanisms underlying this phenomenon are poorly understood but may be mediated via cytokine signalling, particularly JAK dependent pathways. Herein we have explored the effects of IL-6 receptor blockade upon cholesterol metabolism in a clinical experimental study using tocilizumab. Objectives: We sought to define the metabolic pathways (i.e. synthesis versus clearance) whereby specific inhibition of IL-6R signalling in patients with active RA modulates circulating LDL levels. Methods: We performed kinetic studies of LDL metabolism in 12 patients with severe, active RA (DAS28 ≥5.1) eligible for biologic DMARD therapy – one patient withdrew from the study and did not contribute evaluable data. A stable isotope of d3-leucine was administered and incorporated into newly-synthesised apoB; the formation and catabolic rates of apoB-containing lipoproteins were then assessed using an established multi-compartmental model. Kinetic studies were performed at baseline and after at least three consecutive infusions of IV tocilizumab 8mg/kg every 4 weeks. Changes in kinetic parameters (fractional catabolic and synthesis rates, FCR and FSR, respectively), serum lipids and measures of disease activity from baseline were assessed using student's t-test or Wilcoxon matched-pairs test as dictated by normality of data. Correlations between parameters were assessed by Pearson's or Spearman's coefficient as appropriate. Results: In 11 evaluable patients who completed the study, profound reductions were observed after treatment in mean CRP (19 vs 0.75 mg/l, p=0.015) and ESR (38 vs 3mm/hr, p=0.004), with significant changes in CDAI (29.9 v 8.0, p<0.001). Elevations were seen in total cholesterol (4.9 vs 5.7mmol/l, p=0.003), HDL-cholesterol (1.2 vs 1.6mmol/l, p=0.006) and LDL-cholesterol (2.9 vs 3.5mmol/l, p=0.014). The FCR of LDL fell significantly following IL-6 blockade (median 0.53 vs 0.27 pools/day, p=0.006, with median change of -30% from baseline). No significant change was observed in the FSR of LDL (median 0.45 vs 0.72 mg/kg/day, p=0.41). FCR correlated inversely with LDL-c at baseline (r=-0.77, p=0.007) and after treatment (r=-0.66, p=0.031). At baseline, FCR also associated with CRP (r=0.74, p=0.012), but not CDAI (r=0.04, p=0.91). Conclusions: IL-6 blockade increases serum LDL-c primarily by reducing the fractional catabolic rate of LDL from a state of hypercatabolism to levels seen previously in healthy cohorts. Of note, FCR of LDL is most closely associated with the acute phase response rather than with RA disease activity as quantified by CDAI. Normalisation of this acute phase-driven increased catabolism largely explains the LDL-c elevations observed following tocilizumab therapy. Our study for the first time clearly defines IL-6 as the key driver of the increased catabolism of LDL which results in low serum LDL-c levels in RA. Disclosure of Interest: None declared